Železobetonová monolitická vícepatrová skeletová konstrukce - Luža, Radim (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem této diplomové práce je statické řešení vybraných nosných konstrukcí polyfunkčního domu. Konstrukce jsou navržené dle ČSN EN 1992-1-1: Navrhování betonových konstrukcí – Část 1-1: Obecná pravidla a pravidla pro pozemní stavby

The subject of this diploma thesis is a static solution of selected load-bearing structures of a polyfunctional building. The structures are designed according with ČSN EN 1992-1-1: Design of concrete structures - Part 1-1: General rules and rules for building construction
Monolithic multi-storey concrete frame structure
Keywords: Lokálně podepřená stropní deska; železobeton; beton; ocel; ocelová výztuž; statická analýza; dimenzování; výkresová dokumentace; zatížení; posouzení; železobetonová monolitická konstrukce; schodiště; sloupy; Locally supported floor slab; reinforced concrete; concrete; steel; reinforcing steel; structural analysis; dimensioning; drawings; loads; check; reinforced concrete place construction; staircase; columns